Arquitetura de processos com a metodologia business process management como base na automatização dos departamentos em empresa organizadora de concursos - Barros, Anderson Rocha de (2016)
All businesses have processes that define how a product or service will be delivered. Therefore, knowledge of the business process is an important factor to deliver to customers, satisfactory results and get the desired profit. A methodology that contributes to the understanding of this process is known as BPM (Business Process Management) that, through the Process Architecture technique helps in understanding of critical processes, organizing them for a better flow of information, resulting in effective communication among those involved in process of a company. This study was applied to an organizer of tender that, after consecutive errors in the application of an objective test, required that its procedures were revised and improved. With the application of Process Architecture and Business Process Mangement, it was possible to identify problems, organize them and develop a system, automating the improved process in the departments of the company organizing contests. Several applications of objective tests were performed after the process improvement and as a result, the company organizing contests showed no more mistakes and retain many customers.